ADVANCED ANALYTICAL TECHNIQUES FOR NEXT GENERATION SEQUENCING: A NARRATIVE REVIEW - Tara, Tanveer; Kamran, Kamran; Ullah, Zakir; Aziz, Sajid; Mehmood, Asif (Annals of Allied Health Sciences, 2019)
The objective of current study was to provide historical perspective of DNA sequencing with focus on newer developments especially the sequencing techniques under the umbrella of next generation sequencing (NGS). Several methods of sequencing were compared based on time consuming, complexity of process, cost effectiveness, reading of base pairs per seconds/minutes, rate of errors, high quality and accuracy.Comparison of various sequencing techniques including sanger’s sequencing, next generation sequencing and third generation sequencing were discussed in current review. Other sub-sequencing techniques of next generation sequencing were also described, in which Illumina sequencing was determined good range short read sequencing method with 300bp. 454 and ION torrent techniques was comparatively high read lengths. GeneReader is fully automated from sample preparation to analysis of sample. On the side, PacBio was less time consuming in long read sequencing techniques. This paper provides enhanced understanding and judgmental comparison among different variants of sequencing technologies.